2012
DOI: 10.1021/jp303352h
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Assisted Self-Assemblies of Linear Di-Pyridyl Polyaromatic Molecules at Solid/Liquid Interface

Abstract: Proton-assisted self-assemblies of three linear dipyridyl polyaromatic molecules, namely, 4,4′-bipyridine, 1,4-di(4-pyridyl)-benzene, and 4,4′-di(4-pyridyl)biphenyl, at the heptanoic acid/highly oriented pyrolytic graphite interface were systematically studied with scanning tunneling microscopy. A major finding was that protons from strong acids could greatly accelerate the assembling processes of 4,4′-bipyridine and 1,4-di(4-pyridyl)benzene molecules and, in the case of 4,4′-di(4-pyridyl)biphenyl molecule, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Wu et al reported that assembly at a liquid/solid interface could be efficiently accelerated by protons in the solution phase. 89 A highly ordered self-assembled structure of a neutral bipyridyl compound (P3) was formed at the heptanoic acid/ HOPG interface within 4-6 hours, whereas the same structure was formed within minutes in the presence of protons (Fig. 7A).…”
Section: Catassembly Could Be Homogeneous or Heterogeneousmentioning
confidence: 97%
“…Wu et al reported that assembly at a liquid/solid interface could be efficiently accelerated by protons in the solution phase. 89 A highly ordered self-assembled structure of a neutral bipyridyl compound (P3) was formed at the heptanoic acid/ HOPG interface within 4-6 hours, whereas the same structure was formed within minutes in the presence of protons (Fig. 7A).…”
Section: Catassembly Could Be Homogeneous or Heterogeneousmentioning
confidence: 97%
“…Of particular interest is the protonation-assisted self-assembly to construct smart functional materials. Protonation triggers conformational transitions to induce favorable geometry for self-assembly through charge transfer or pH-dependent molecular stabilization and counteranion interactions. Molecular design involving N-heterocycle ring with basic nitrogen atom offers the most possibility of protonation of the lone pair as a way of modifying structural orientation and facilitate directed intermolecular interactions for the self-assembly process. Pyridine ring represents an important building block, which forms pyridinium complex and induces multiple molecular interactions to assist the self-assembly process. , The protonation of nitrogen atom creates the positive charge on the pyridine ring, which, in turn, activates the α-H and β-H in the pyridine ring, making them stronger hydrogen-bonding donors. The competing attractive forces arising from the counterions and/or hydrogen bonding involving the pyridine ring balances the total system charge, which leads to a favorable molecular association. Most importantly, protonation-induced self-assembly can often be reverted by reversing the triggering stimuli upon deprotonation and thus provide an opportunity to generate a reversible assembly-related functional response by simply alternating the addition of acid and base. …”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly of two-dimensional (2D) supramolecular structures driven by the formation of weak C–H···O, C–H···F, , and C–H···N bonding and their combination with O–H···O bonds has been observed on solid surfaces. C–H···N interactions are known to occur between pyridine derivatives and other nitrogen-containing molecular building blocks .…”
Section: Introductionmentioning
confidence: 99%